Erosive wear performance of boron-doped diamond films on different substrates. (March 2014) - Wang, Xinchang; Cui, Yuxiao; Zhang, Jianguo; Shen, Bin; Sun, Fanghong
Diamond films have been considered as good candidate protective coatings on varieties of substrates in order to improve their erosive wear performance. In the present study, boron-doped diamond films with thicknesses of about 6–7 µm are first deposited on five different substrates using the hot filament chemical vapor deposition method, including SiC, WC-Co, Ta, Ti, and Si substrates. The residual stress and adhesive strength of the five boron-doped diamond films are estimated, respectively, by means of material properties of substrates and the diamond, Raman spectra, and static indentation results. Erosion tests are conducted on all the boron-doped diamond coated samples in an air–sand erosion rig with angular SiC sands as erodents. The results exhibit that the formation of ring cracks on the boron-doped diamond film in the erosion process has a strong link to the total residual stress. The higher residual compressive stress in the Ti-based boron-doped diamond film can slow down the formation of ring cracks to some extent. Nevertheless, the erosive wear performance, which is mainly evaluated based on the erosion rate and film removal, is much related to the film–substrate adhesion. As a result, the Ti-based boron-doped diamond film is quickly worn and removed because of the poorest adhesion. On the contrary, both the SiC- and Si-based boron-doped diamond films with favorable adhesion perform much better erosion resistance. Moreover, comparative erosion tests on thicker SiC- and WC-Co-based boron-doped diamond films (21–23 µm) and their applications on nozzles can both further manifest the same kind of relationship, the SiC-based boron-doped diamond film presenting longer steady erosive stage and slower film removal than the WC-Co-based one.